Single-Parent Families in Singapore: Understanding the Challenges of Finances, Housing and Time Poverty - Glendinning, Emma (Institutional Knowledge at Singapore Management University, 2015)
This publication documents the unmet social needs of single-parent families in Singapore. It specifically focuses on four key areas; employment and finance, housing, social networks and time poverty. In-depth, qualitative interviews were completed with 88 low-income single parents across Singapore. These interviews provided the opportunity to truly explore the stories of these single-parent families, displaying the complexity and interplay of the issues they faced. Our findings display the huge responsibility that single parents carry as they balance the caregiving and financial needs of their family, alongside negotiating policies that are largely suggested to support the “traditional” family structure. While respecting that dignity and pride prevents many individuals approaching family, friends or support services for assistance, this publication offers some suggestions as to how to improve support systems to offer long-term solutions, rather than short term fixes, to the issues faced by single-parent families.